2010
DOI: 10.1016/j.acuro.2009.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Incidencias y complicaciones en nuestras primeras 250 prostatéctomias radicales robóticas

Abstract: Robotic radical prostatectomy is a safe and reproducible procedure with optimal functional and oncological results, a shorter learning curve, greater comfort and vision for surgeons, and a complication rate similar to and even better than reported for open and laparoscopic surgery series. Complications decrease with the learning curve, but surgical team experience continues to be the key factor to achieve better results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 38 publications
0
5
0
1
Order By: Relevance
“…In contrast to decreases in conversion, it seems that patient damage by RM is relatively increased. Whereas before 2009 only one casualty was described among 9 cases of patient damage in 189 adverse events [ 9 ], after 2010 Pereyra et al [ 15 ] and Mues et al [ 17 ] describe 4 and 3 RM related damages, respectively. The latter number only describes instrument failure related RMs, and all three damages were major complications (iliac vein lesions, ileal perforation, and urethral cauterization).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to decreases in conversion, it seems that patient damage by RM is relatively increased. Whereas before 2009 only one casualty was described among 9 cases of patient damage in 189 adverse events [ 9 ], after 2010 Pereyra et al [ 15 ] and Mues et al [ 17 ] describe 4 and 3 RM related damages, respectively. The latter number only describes instrument failure related RMs, and all three damages were major complications (iliac vein lesions, ileal perforation, and urethral cauterization).…”
Section: Discussionmentioning
confidence: 99%
“…Yi et al [10] recently reported 4 further cases of metal clip migration after RRP; two resulted in stone formation and the other two into BNC. There are few reports of hem-o-lok clip migration into the urinary tract leading to spontaneous expulsion, urethral erosion, bladder stone formation and bladder neck contracture [1-7]. These findings would suggest that the use of clips in proximity of the vesico-urethral anastomosis should be limited if not avoided, and that the occurrence of de novo voiding symptoms in patients having undergone radical prostatectomy should rise the suspect of clip-related complications.…”
Section: Case Presentationmentioning
confidence: 99%
“…Their migration into the urinary tract has already been described [1-7], presenting with spontaneous expulsion, urethral erosion, bladder stone formation and even bladder neck contracture (BNC). There is no previous report of stress urinary incontinence (SUI) following removal of a migrated hem-o-lok clip.…”
Section: Introductionmentioning
confidence: 99%
“…In order to decrease the rate of lymphocele, meticulous lymphostasis is critical and can be achieved with the use of titanium clips. Unfortunately, significant complications have been associated with the use of common non-absorbable clips including clip migration into the bladder and rectum following RP ( 30 ). All of these complications required additional procedures for clip removal with some leading to permanent functional impairment.…”
Section: Developing a Personalized Template For Lnd In Capmentioning
confidence: 99%